2014
DOI: 10.1016/j.rasd.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Schematic and realistic biological motion identification in children with high-functioning Autism Spectrum Disorder

Abstract: Research investigating biological motion perception in children with ASD has revealed conflicting findings concerning whether impairments in biological motion perception exist. The current study investigated how children with high-functioning ASD (HF-ASD) performed on two tasks of biological motion identification: a novel schematic motion identification task and a point-light biological motion identification task. Twenty-two HFASD children were matched with 21 TD children on gender, non-verbal mental, and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
(105 reference statements)
1
10
1
Order By: Relevance
“…Given the pictures of nonsocial threats included pictures of snakes only, it is interesting that the early microstates elicited in lonely individuals by social threats tend to reflect attention and the orchestration of responses to threat, whereas the early microstates elicited by nonsocial threats tend to reflect the more nuanced processes of social perception and episodic memory. The present involvement of brain areas sustaining biological motion perception is in line with the fact that the nonsocial threat stimuli, such as pictures of snakes, are known to invoke a schematic biological identification (even in the absence of local image motion; Beintema & Lappe, 2002), as they correspond to a biological threat known to produce a visceral fear response in the majority of individuals (Wright, Kelley, & Poulin-Dubois, 2014). …”
Section: Discussionsupporting
confidence: 74%
“…Given the pictures of nonsocial threats included pictures of snakes only, it is interesting that the early microstates elicited in lonely individuals by social threats tend to reflect attention and the orchestration of responses to threat, whereas the early microstates elicited by nonsocial threats tend to reflect the more nuanced processes of social perception and episodic memory. The present involvement of brain areas sustaining biological motion perception is in line with the fact that the nonsocial threat stimuli, such as pictures of snakes, are known to invoke a schematic biological identification (even in the absence of local image motion; Beintema & Lappe, 2002), as they correspond to a biological threat known to produce a visceral fear response in the majority of individuals (Wright, Kelley, & Poulin-Dubois, 2014). …”
Section: Discussionsupporting
confidence: 74%
“…Non-biological motion in ASD vs. TD . This meta-analysis is limited to the studies that test, together with the perception of a BM stimulus, also the processing of another stimulus that can be defined as a non-BM stimulus (i.e., an object as a bike or a truck presented in PLD 109,112 or of a scrambled version of the BM stimulus 39,113,114 (n = 5). It is important to note that we do not consider this analysis to be ultimately conclusive, because an extensive analysis of this type should include also other types of non-BM tasks such as coherent motion, form-from-motion, etc.…”
Section: Impact Of Low-level Features Of Bm Scrambled Stimuli In Asd mentioning
confidence: 99%
“…We observed no evidence of impairments in the processing of non-BM stimuli in individuals with ASD; this suggests that the deficit is selective for BM stimuli and to their specific spatio-temporal pattern, whereas other types of complex stimuli in motion do not elicit a similar impairment. Among the non-BM tasks tested, we can find recognition/categorization of an object as a bike or a truck presented in PLD (Hubert et al, 2007;Wright et al, 2014) but also recognition/categorization of a scrambled version of the BM stimulus (Herrington et al, 2007;Kröger et al, 2014;Murphy et al, 2009). It is clear however that testing the scrambled version of BM stimuli is not ideal to claim that the deficit observed in individuals with ASD is specific to stimuli moving in a biological fashion.…”
Section: Is the Impairment Observed In Asd Specific To Biological Motmentioning
confidence: 97%
“…were only two studies that tested non-BM processing using tasks where the form was preserved (Hubert et al, 2007;Wright et al, 2014). These two studies, however, found no clear evidence of impairments in participants with ASD, independently of the nature of the moving stimuli (BM vs. non-BM) employed.…”
Section: Is the Impairment Observed In Asd Specific To Biological Motmentioning
confidence: 98%
See 1 more Smart Citation